Human Atrial Fibroblast Adaptation to Heterogeneities in Substrate Stiffness - Emig, Ramona; Zgierski-Johnston, Callum M.; Beyersdorf, Friedhelm; Rylski, Bartosz; Ravens, Ursula; Weber, Wilfried; Kohl, Peter; Hörner, Maximilian; Peyronnet, Rémi (Frontiers in Physiology, 2020)
Fibrosis is associated with ageing and many cardiac pathologies. It is characterized both by myofibroblast differentiation and by excessive accumulation of extracellular matrix proteins. Fibrosis-related tissue remodeling results in significant changes in tissue structure and function, including passive mechanical properties. This research area has gained significant momentum with the recent development of new tools and approaches to better characterize and understand the ability of cells to sense and respond to their biophysical environment. We use a novel hydrogel, termed CyPhyGel, to provide an advanced in vitro model of remodeling-related changes in tissue stiffness. Based on light-controlled dimerization of a Cyanobacterial Phytochrome, it enables contactless and reversible tuning of hydrogel mechanical properties with high spatial and temporal resolution. Human primary atrial fibroblasts were cultured on CyPhyGels. After four days of culturing on stiff (~4.6 kPa) or soft (~2.7 kPa) CyPhyGels, we analyzed fibroblast cell area and stiffness. Cells grown on the softer substrate were smaller and softer, compared to cells grown on the stiffer substrate. This difference was absent when both soft and stiff growth substrates were combined in a single CyPhyGel, with the resulting cell areas being similar to that those on homogeneously stiff gels and cell stiffnesses being similar to those on homogeneously soft substrates. By using CyPhyGels to mimic tissue stiffness heterogeneities in vitro, our results confirm the ability of cardiac fibroblasts to adapt to their mechanical environment, and suggest the presence of a paracrine mechanism that tunes fibroblast structural and functional properties associated with mechanically induced phenotype conversion towards myofibroblasts. In the context of regionally increased tissue stiffness, such as upon scarring or in diffuse fibrosis, such a mechanism could help to prevent abrupt changes in cell properties at the border zone between normal and diseased tissue. The light-tunable mechanical properties of CyPhyGels and their suitability for studying human primary cardiac cells make them an attractive model system for cardiac mechanobiology research. Further investigations will explore the interactions between biophysical and soluble factors in the response of cardiac fibroblasts to spatially and temporally heterogeneous mechanical cues.